Vorinostat suppresses hypoxia signaling by modulating nuclear translocation of hypoxia inducible factor 1 alpha - Zhang, Chao (Oncotarget, 2017)
Histone deacetylase inhibitors (HDACis) are a potent class of tumor-suppressive agents traditionally believed to exert their effects through loosening tightly-wound chromatin resulting in de-inhibition of various tumor suppressive genes. Recent literature however has shown altered intratumoral hypoxia signaling with HDACi administration not attributable to changes in chromatin structure. We sought to determine the precise mechanism of HDACi-mediated hypoxia signaling attenuation using vorinostat (SAHA), an FDA-approved class I/IIb/IV HDACi. Through an in-vitro and in-vivo approach utilizing cell lines for hepatocellular carcinoma (HCC), osteosarcoma (OS), and glioblastoma (GBM), we demonstrate that SAHA potently inhibits HIF-a nuclear translocation via direct acetylation of its associated chaperone, heat shock protein 90 (Hsp90). In the presence of SAHA we found elevated levels of acetyl-Hsp90, decreased interaction between acetyl-Hsp90 and HIF-a, decreased nuclear/cytoplasmic HIF-α expression, absent HIF-α association with its nuclear karyopharyin Importin, and markedly decreased HIF-a transcriptional activity. These changes were associated with downregulation of downstream hypoxia molecules such as endothelin 1, erythropoietin, glucose transporter 1, and vascular endothelial growth factor. Findings were replicated in an in-vivo Hep3B HRE-Luc expressing xenograft, and were associated with significant decreases in xenograft tumor size. Altogether, this study highlights a novel mechanism of action of an important class of chemotherapeutic.